Evaluating training impacts in conservation through a case study in Mauritius - Milner-Gulland, E; Sawrey, B; Copsey, J (Cambridge University Press, 2017)
The need for increased monitoring and evaluation within the conservation sector has been well documented; this includes the monitoring and evaluation of training activities. This study evaluates the impacts of a long-term training programme in Mauritius using a questionnaire and semi-structured key informant interviews to develop a theory of change from the perspective of the trainers, and validate it against participants' perceptions of the benefits of training. Findings suggest that an important outcome of training is to increase participants’ belief that they can effect change, also called perception of control; this aspect links to an increase in a trainee’s practical skills, enabling them to become more effective in their work. However, if a trainee’s work environment was negative, the impact of training on practical skills, job performance and perception of control was lower. Neither the acquisition of conservation theory nor the opportunity to network was perceived by participants as improving their conservation performance, despite trainers anticipating that they would be important. Perception of control and work environment should therefore be carefully considered when designing conservation training programmes, and the effectiveness of teaching conservation theory and networking should be further examined.